2019
DOI: 10.1002/smll.201804688
|View full text |Cite
|
Sign up to set email alerts
|

Multishelled Hollow Structures of Yttrium Oxide for the Highly Selective and Ultrasensitive Detection of Methanol

Abstract: Methanol is extremely harmful to human health, since it is oxidized slowly and can accumulate in the human body. Therefore, it is essential to develop a methanol gas sensing technology with high sensitivity and selectivity for use in environmental monitoring and healthcare. In this work, a simple and low‐cost sensor based on a Y2O3 multishelled hollow structure (YMSH) to selectively detect methanol with an ultrasensitive limit of detection (71 ppb) is developed. The unique multishelled hollow structure with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 73 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…Recently, Zheng et al reported Y 2 O 3 multishelled hollow structures with exposed {220} facets, which makes a significant contribution to the detection of methanol with ultrahigh sensitivity and selectivity. 225 It has been reported that the performance of semiconductorbased gas sensors may be further enhanced by loading uniform noble metal nanoparticles. [226][227][228] Yoon and co-workers prepared Pd-loaded quintuple-shelled Co 3 O 4 microspheres via spray drying followed by thermal treatment.…”
Section: Template-free Methodsmentioning
confidence: 99%
“…Recently, Zheng et al reported Y 2 O 3 multishelled hollow structures with exposed {220} facets, which makes a significant contribution to the detection of methanol with ultrahigh sensitivity and selectivity. 225 It has been reported that the performance of semiconductorbased gas sensors may be further enhanced by loading uniform noble metal nanoparticles. [226][227][228] Yoon and co-workers prepared Pd-loaded quintuple-shelled Co 3 O 4 microspheres via spray drying followed by thermal treatment.…”
Section: Template-free Methodsmentioning
confidence: 99%
“…With the development of material science, many advanced nanomaterials have been introduced into the design of CTL-based sensor. For instance, F-doped cage-like SiC-based sensors for hydrogen sulfide [ 25 ], Y-doped metal-organic framework-5-based sensors for iso-butanol [ 26 ], sensors based on hydrotalcite-supported gold nanoparticles for acetaldehyde [ 27 ], and sensors based on Y 2 O 3 with multi-shelled hollow structure for methanol [ 28 ]. The expanded availability of nanomaterials has greatly advanced the development of CTL-based sensors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al 17 synthesized Cu 2 O microspheres with multilayered and porous shells; the synthesized material showed much higher sensitivity to ethanol than solid Cu 2 O microspheres. Zheng et al 18 reported a methanol sensor based on a Y 2 O 3 multishell hollow structure with an ultrasensitive limit of 71 ppb. Despite its acceptable sensitivity, pristine MOSs have poor selectivity and a high detection limit, and it is difficult to resolve these issues only through morphological modulation.…”
mentioning
confidence: 99%
“…For example, Zhang et al synthesized Cu 2 O microspheres with multilayered and porous shells; the synthesized material showed much higher sensitivity to ethanol than solid Cu 2 O microspheres. Zheng et al reported a methanol sensor based on a Y 2 O 3 multishell hollow structure with an ultrasensitive limit of 71 ppb.…”
mentioning
confidence: 99%